CFTR transcripts are undetectable in lymphocytes and respiratory epithelial cells of a CF patient homozygous for the nonsense mutation R553X. Issue 10 (October 1993) - Will, K; Reiss, J; Dean, M; Schlösser, M; Slomski, R; Schmidtke, J; Stuhrmann, M
Abstract : In order to analyse the influence of the nonsense mutation R553X on CFTR gene expression, transcripts from epithelial cells and lymphocytes were examined from nine subjects (one CF patient homozygous for R553X, one CF patient compound heterozygous for R553X/delta F508, four CF carriers heterozygous for R553X, one CF carrier with the genotype delta F508/N, and two uncharacterized normal adults). After reverse transcription of the region from exons 10 to 13 to cDNA, fragments of the expected size were amplified from all heterozygous and normal subjects. In three subjects an additional alternatively spliced product was observed, which was found to contain a termination codon. In repeated experiments it was not possible to detect any CFTR mRNA in cells derived from the R553X homozygous patient. Furthermore, in subjects heterozygous for R553X we could not detect by hybridisation with a specific oligonucleotide probe and direct sequencing any CFTR mRNA derived from the R553X allele. However, the wild type product was present in all of these subjects. Our results support the view that nonsense mutations in the CFTR gene can lead to a reduction or absence of cytoplasmic CFTR mRNA.